Diversity of Bacterial Photosymbionts in Lubomirskiidae Sponges from Lake Baikal. (20th November 2014) - Kulakova, Nina V.; Denikina, Natalia N.; Belikov, Sergei I.
Abstract : Sponges are permanent benthos residents which establish complex associations with a variety of microorganisms that raise interest in the nature of sponge-symbionts interactions. A molecular approach, based on the identification of the 16S rRNA and ribulose-1, 5-bisphosphate carboxylase/oxygenase large subunit genes, was applied to investigate diversity and phylogeny of bacterial phototrophs associated with four species of Lubomirskiidae in Lake Baikal. The phylogeny inferred from both genes showed three main clusters of Synechococcus associated with Baikalian sponges. One of the clusters belonged to the cosmopolitan Synechococcus rubescens group and the two other were not related to any of the assigned phylogenetic groups but placed as sister clusters to S. rubescens . These results expanded the understanding of freshwater sponge-associated photoautotroph diversity and suggested that the three phylogenetic groups of Synechococcus are common photosynthetic symbionts in Lubomirskiidae sponges.